THE OUTCOME OF ANTIBIOTIC THERAPY AMONG CHILDREN WITH SEVERE COMMUNITY ACQUIRED PNEUMONIA - Usman, M. R.; Wati, D. K.; Subanada, I. B. (BALI MEDICAL JOURNAL; Vol 4 No 2 (2015), 2015)
Background: The effect of human immunodeficiency virus (HIV) status on the evolution of community acquired pneumonia (CAP) is still controversial. There are controversies regarding antibiotic treatment outcome of CAP in HIV infected children. Objective: The aim of this study was to investigate possible differences in hospital outcomes, with compared the outcome of the treatment in severe CAP among HIV infected and HIV uninfected children which had an empiric antibiotic therapy. Methods: A case control study of 80 patients with severe CAP in Department of Child Health, Sanglah General Hospital, Bali-Indonesia. We evaluated clinical features for seeing the effectiveness of the antibiotic therapy according to Department of Child Health, Sanglah General Hospital’s clinical pathway for severe pneumonia between HIV infected and HIV uninfected patients. Results: 58% patients in failure treatment and 45% patients in favorable treatment were HIV infected. There were similar characteristics from both groups, except malnutrition condition was statistically significant contribute the outcome (OR 2.87 (95% CI 1.098 to 7.500, p= 0.031). There was no significantly statistic difference of the outcome in HIV infected as compared to HIV uninfected patients with severe CAP (OR 1.65 (95% CI 0.683 to 4.002, p= 0.263). Conclusion: HIV infection was not gave an effect on the outcome of severe CAP patients which had an antibiotic therapy based on Department of Child Health, Sanglah General Hospital’s clinical pathway for severe pneumonia.
Keywords: Community acquired pneumonia, HIV infection, Antibiotic, Outcome, Children